If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(q + -1) = 6q + 2 + 3q Reorder the terms: 6(-1 + q) = 6q + 2 + 3q (-1 * 6 + q * 6) = 6q + 2 + 3q (-6 + 6q) = 6q + 2 + 3q Reorder the terms: -6 + 6q = 2 + 6q + 3q Combine like terms: 6q + 3q = 9q -6 + 6q = 2 + 9q Solving -6 + 6q = 2 + 9q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-9q' to each side of the equation. -6 + 6q + -9q = 2 + 9q + -9q Combine like terms: 6q + -9q = -3q -6 + -3q = 2 + 9q + -9q Combine like terms: 9q + -9q = 0 -6 + -3q = 2 + 0 -6 + -3q = 2 Add '6' to each side of the equation. -6 + 6 + -3q = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -3q = 2 + 6 -3q = 2 + 6 Combine like terms: 2 + 6 = 8 -3q = 8 Divide each side by '-3'. q = -2.666666667 Simplifying q = -2.666666667
| 19-4x=-6x+9 | | x+11=-9x-7 | | 13x+8=y | | -15w-19=-14w | | 15l+5.50p=100 | | x^3-3x^2-2x=6 | | 2x+2=-(4x+6)-2x | | 7-4=10x+3 | | -44=-2(x+14) | | 300=7x-(100+3x) | | 3/2+2m/5=29/10 | | 3x+6+7x-18=90 | | 50-20x=30+30x | | 1/3v=-132 | | -3-4x=4x-35 | | f(x)=2-5x | | -3s=-2s-8 | | 10x-12=90 | | 3v^2+2v-1=0 | | 59+9s=400 | | 6d+10=8d-8 | | 3x+6=6x(8+9) | | -2(1/2r-5)=1.25+0.25r | | 5x+2x-6=8 | | -3x-4.7=11.8 | | 8-2r=16 | | -19=2x+32 | | 3(5x-8)=36 | | 37.91=8g+3.59 | | y/4=72 | | P=7x-(100+3x) | | 3x+6(4x-1)=4-9x |